2015
DOI: 10.1016/j.energy.2015.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the energy and exergy efficiencies of farm to fork grain cultivation and bread making processes in Turkey and Germany

Abstract: Energy and exergy efficiencies of the wheat and rye bread and hamburger bun making processes are assessed based on data from Turkey and Germany. Amount of the land required to produce the same amount of wheat in Turkey is 3.34 times of that required in Germany; this ratio is 2.30 for the rye grain. These results show that the efficiency of the conversion of the solar energy into the grain mass is low in Turkey. Cumulative degree of perfection (CDP) for the wheat and the rye grain production is 3.73 and 4.96 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“… had 33, and Değerli et al . had 110 references. The other major changes occurring within this period were the nature of the data and the depth of information needed.…”
Section: Sources Standards and Quality Of The Biothermodynamics Datamentioning
confidence: 99%
See 2 more Smart Citations
“… had 33, and Değerli et al . had 110 references. The other major changes occurring within this period were the nature of the data and the depth of information needed.…”
Section: Sources Standards and Quality Of The Biothermodynamics Datamentioning
confidence: 99%
“…Ways to increase the photosynthetic efficiency of plants are being actively researched to improve their yields, including improvement of the efficiency of the photosynthesis to increase crop yields of the plants, especially grain crops [51]. Değerli et al [52], after performing the assessment of energy and exergy efficiencies of farm to fork grain cultivation and bread-making processes in Turkey and Germany, concluded that the amount of land required to produce the same amount of wheat in Turkey is 3.34 times of that required in Germany; this ratio is 2.30, with rye pointing to the lower efficiency of the conversion of the solar energy into grain mass in Turkey. The ratio of the values of the cumulative degree of performances achieved in Germany to those achieved in Turkey was 3 with the wheat grain and 2 with the rye grain, indicating the higher level of renewability of German agriculture.…”
Section: Source Of the Bioenergymentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Genc and Hepbasli [21] evaluated the exergetic performance of a potato crisp frying system including three main components, i.e., combustor, heat exchanger, and fryer. In the same year, Degerli et al [22] assessed wheat and rye bread and hamburger bun making processes using farm-to-fork approach based on data obtained from Turkey and Germany. Recently, Jafaryani Jokandan et al [5] carried out a comprehensive exergy analysis of an industrial-scale yogurt processing plant.…”
Section: Introductionmentioning
confidence: 99%
“…As there are still a limited number of thermodynamic data for organic compounds available in the literature, it is of great interest to use reliable methods for property estimation if experimental measurements cannot be performed. The use of group contribution methods (GC) has been reported in the literature for the estimation of chemical exergy of organic compounds such as proteins (Sorgüven and Özilgen 2012), antigens (Değerli et al 2015a), wheat seeds and agro-chemicals (Değerli et al 2015b). Studies by Joback and Reid (1987), Constantinou and Gani (1994), Marrero and Gani (2001) and Gharagheizi et al (2014Gharagheizi et al ( , 2018 contributed substantially to the development of this estimation method.…”
Section: Introductionmentioning
confidence: 99%